Efficient Usage of RGB-LED for Optical Wireless Communication - Bui, Thai-Chien; Sriphan, Saichon; Kiravittaya, Suwit (Naresuan University Journal: Science and Technology (NUJST), 2016)
Light-emitting diode (LED) can be used as a sensitive optical sensor for a variety of applications. In some applications such as LED-to-LED communication, LED must be able to detect light in visible range. The color of the emitting and sensing LED is an important parameter. In this paper, the influence of LED color in an RGB-LED for optical sensing and emitting in short-range optical wireless communication is investigated. The electrical characteristics of the RGB-LED are analyzed in the static and dynamic response modes. The current-voltage, capacitance-voltage and frequency-dependent capacitance characteristics are measured. From these results, we found that the red color of RGB-LED have the lowest capacitance in reverse biased condition. Therefore, they can be used as an efficient receiver in our proposed visible light range. Performance of RGB-LEDs is then tested with a simple optical wireless communication setup. The results show that only the red and green color of the RGB-LED can efficiently be used for detecting light in visible range. The highest communication speed of 3.5 kbps (with a bit error rate below 10 -3 ) is achieved when the red color LED is used for sensing green light. Keywords : Light-emitting diode, Visible light communication, Electrical characteristics, Optical communication
Keywords: Light-emitting diode, Visible light communication, Electrical characteristics, Optical communication